High Microbial Diversity Promotes Soil Ecosystem Functioning - Maron, Pierre-Alain; Sarr, Amadou; Kaisermann, Aurore; Lévêque, Jean; Mathieu, Olivier; Guigue, Julien; Karimi, Battle; Bernard, Laetitia; Dequiedt, Samuel; Terrat, Sébastien; Chabbi, Abad; Ranjard, Lionel (Applied and environmental microbiology, 2018)
In soil, the link between microbial diversity and carbon transformations is challenged by the concept of functional redundancy. Here, we hypothesized that functional redundancy may decrease with increasing carbon source recalcitrance and that coupling of diversity with C cycling may change accordingly. We manipulated microbial diversity to examine how diversity decrease affects the decomposition of easily degradable (i.e., allochthonous plant residues) versus recalcitrant (i.e., autochthonous organic matter) C sources. We found that a decrease in microbial diversity (i) affected the decomposition of both autochthonous and allochthonous carbon sources, thereby reducing global CO 2 emission by up to 40%, and (ii) shaped the source of CO 2 emission toward preferential decomposition of most degradable C sources. Our results also revealed that the significance of the diversity effect increases with nutrient availability. Altogether, these findings show that C cycling in soil may be more vulnerable to microbial diversity changes than expected from previous studies, particularly in ecosystems exposed to nutrient inputs. Thus, concern about the preservation of microbial diversity may be highly relevant in the current global-change context assumed to impact soil biodiversity and the pulse inputs of plant residues and rhizodeposits into the soil. IMPORTANCE With hundreds of thousands of taxa per gram of soil, microbial diversity dominates soil biodiversity. While numerous studies have established that microbial communities respond rapidly to environmental changes, the relationship between microbial diversity and soil functioning remains controversial. Using a well-controlled laboratory approach, we provide empirical evidence that microbial diversity may be of high significance for organic matter decomposition, a major process on which rely many of the ecosystem services provided by the soil ecosystem. These new findings should be taken into account in future studies aimed at understanding and predicting the functional consequences of changes in microbial diversity on soil ecosystem services and carbon storage in soil.